Analysis of Entrepreneurial Orientation, Environmental Adaptability, and Strategic Orientation on Business Performance Through the Mediation of Competitive Advantage - Berliana, Ling Ling; Toto Raharjo, Susilo (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
This study aims to analyze the influence of entrepreneurial orientation, business environment adaptability, and strategic orientation on competitive advantage and business performance, and to examine the mediating role of competitive advantage. The research involved 66 coffee shop entrepreneurs in Tegal Regency selected through purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results show that entrepreneurial orientation significantly affects competitive advantage (0.253; t = 2.273; p = 0.025) and business performance (0.268; t = 2.281; p = 0.023). Business environment adaptability also significantly influences competitive advantage (0.434; t = 4.125; p = 0.000) and business performance (0.237; t = 1.984; p = 0.048). Strategic orientation has a positive effect on competitive advantage (0.362; t = 3.236; p = 0.001) and business performance (0.238; t = 1.994; p = 0.046). Competitive advantage significantly affects business performance (0.362; t = 2.736; p = 0.006) and mediates the influence of entrepreneurial orientation (p = 0.039), environmental adaptability (p = 0.035), and strategic orientation (p = 0.031) on business performance. These findings highlight the importance of competitive advantage as a mediating and strategic factor in improving business performance in dynamic market environments